2003
DOI: 10.1046/j.1528-1157.2003.32902.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topiramate in Two Models of Genetically Determined Generalized Epilepsy, the GAERS and the Audiogenic Wistar AS

Abstract: Summary:Purpose: The antiepileptic effects of topiramate (TPM) were assessed in two models of genetically determined generalized epilepsy. The model of nonconvulsive epilepsy used was a model of absence seizures, the GAERS (Genetic Absence Epilepsy Rat from Strasbourg); and the model of convulsive seizures was an audiogenic rat model, the Wistar Audiogenic Sensitive (AS) rat.Methods: GAERS were equipped with four cortical electrodes over the frontoparietal cortex, and the duration of spikeand-wave discharges (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…In the chronic VNS experiment, cumulative SWD duration was significantly reduced in the VNS group, but the effect was very similar in the control group, where it just did not reach significance. A previously reported spontaneous reduction of seizures in GAERS may be an interfering factor (17,18). This phenomenon is correlated with the decrease of vigilance resulting in more sleep episodes and less and shorter seizures (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the chronic VNS experiment, cumulative SWD duration was significantly reduced in the VNS group, but the effect was very similar in the control group, where it just did not reach significance. A previously reported spontaneous reduction of seizures in GAERS may be an interfering factor (17,18). This phenomenon is correlated with the decrease of vigilance resulting in more sleep episodes and less and shorter seizures (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…A previously reported spontaneous reduction of seizures in GAERS may be an interfering factor (17,18). This phenomenon is correlated with the decrease of vigilance resulting in more sleep episodes and less and shorter seizures (17,18). It could also explain the fewer seizures and shorter mean SWD durations that we found in our chronic experiment (Table 1) compared to previously published experiments in GAERS, which were monitored only for a short period of time (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has no significant direct effects on blood sugar, it was found to be effective in several animal seizure models (Shank et al 2000). These include models predictive of efficacy against several human seizure types: tonic-clonic seizures – the rodent maximal electroshock model (Shank et al 1994), complex partial seizures – amygdalar kindling (Wauquier and Zhou 1996), and absence seizures – genetic absence epilepsy rats (Rigoulot et al 2003). …”
Section: Pharmacologymentioning
confidence: 99%
“…However, it has been observed that lamotrigine may cause an increase in myoclonic seizures in JME (Janz syndrome). 63 64 Although topiramate has been shown to have a broad spectrum of anticonvulsant activity in animal experiments, 65 there is insufficient experience with its clinical application in the treatment of primary generalised epilepsies at present, although it has been licensed for this indication in some countries. Smaller, open label studies, anecdotal reports, and one placebo controlled study suggest that topiramate has beneficial effects in generalised epilepsies.…”
Section: Role Of New Antiepileptic Drugs In the Treatment Of Primary mentioning
confidence: 99%